The role of NRARP in the regulation of Wnt signaling pathway in T-cell acute lymphoblastic leukemia - Gonçalves, Joana Margarida Luís (2018)
Tese de mestrado, Biologia Molecular e Genética, Universidade de Lisboa, Faculdade de Ciências, 2018